Multidisciplinary of depression spectrum disorders from a health care system perspective - Ziętara, Karolina Joanna; Pawłowski, Piotr; Chromiak, Karol; Orzechowska, Aleksandra; Michalczyk, Justyna; Orzechowska, Julia (Journal of Education, Health and Sport, 2022)
Introduction: Depression is the leading cause of disability, and incapacity in the world and the most common mental disorder. Year after year, the incidence of this disease entity is increasing, therefore, depression is a serious challenge for modern medicine. Aim of the study: To synthesize the knowledge of depression as a problem in modern medicine. Material and method: A non-systematic review of scientific literature from 2012 - 2022 was carried out, according to the keyword’s depression, symptoms, diagnosis, and treatment. Results and conclusions: Depression is a psychiatric disorder showing varied symptoms lasting more than 2 weeks. Prominent among them are lowered mood, anhedonia, reduced life activities, and others. Diagnosis of depression is difficult, requiring cooperation between the doctor and the patient. Treatment of depression is mainly based on pharmacotherapy and psychotherapy; unconventional treatment is also distinguished.